Common fixed points under Lipschitz type condition - Pant, Vyomesh (Kathmandu University Journal of Science, Engineering and Technology, 2011)
The present paper is aimed at obtaining common fixed point theorems for a pair of selfmaps satisfying nonexpansive or Lipschitz type condition by using the notion of pointwise R- weak commutativity but without assuming the completeness of the space or continuity of the mappings involved. Mathematics Subject Classification: 54 H 25. Key Words and Phrases: Lipschitz type mapping pairs, nonexpansive conditions, noncompatible mappings, Pointwise R-weak commutativity, contractive conditions. DOI: http://dx.doi.org/ 10.3126/kuset.v7i1.5424 KUSET 2011; 7(1): 74-78